“Micropropagación del cultivo de tomate (Salanum lycopersicum L) con diferentes medios de cultivo en el Cantón Cevallos Provincia Tungurahua.”. - González Albarracín, Hermes Adán (2021)
The research was carried out in the biotechnology laboratory "VITRO PLANTA" which is located in San Fernando, Cevallos Canton, Tungurahua province. The tomato (Solanum Lycopersicum L) is one of the crops great importance, the social and economic impact within the families of producers has been declining in the economy, by the proliferation of diseases, which is why its propagation has been affected because after a certain time varietal purity is lost. For this reason, the general objective was to develop the micropropagation of the tomato crop with different culture media and growth hormones. The specific objectives were to establish a micro propagation protocol for the tomato crop and evaluate the appropriate culture media for the in vitro multiplication of the tomato crop. Using a completely randomized design with the following treatments: T1 75% Murashige and Skoog + 25% Aloe +Benzylaminapurine, T2 75% Murashige and Skoog + 25% Aloe +Zeatin, T3 25% Murashige and Skoog + 75% Aloe +Benzylaminapurine, T4 25% Murashige and Skoog + 75% Aloe vera +Zeatin and T5 100% Murashige and Skoog, resulting in T4 25% Murashige and Skoog + 75% Aloe +Zeatin being the most effective in the evaluated variables a large number of shoots, the number of leaves, and in costs, T4 was the best with a profit of 0.69 USD.